2018
DOI: 10.5751/es-10066-230231
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and obstacles to socioecosystem-based environmental policy in Mexico: expert opinion at the science-policy interface

Abstract: ABSTRACT. The urgent need to revert the ecological and social equity crises of the current development model and realize the potential of sustainable development has led several disciplines to converge on the socioecosystem concept as the most appropriate theoretical framework for research and public policy. The socioecosystem approach recognizes that social systems are integrated with natural systems and seeks to adaptively comanage socioecosystem coevolution for the sustainable development of both systems. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
1
4
0
1
Order By: Relevance
“…Besides, in similar studies of abandoned oil sites, infrastructure has been identified, such as valves, incinerators, separation batteries, wells, and waste pits (Trellu et al, 2017), all with very low concentrations of hydrocarbons and, in some cases, spills have been covered by flora or soil (Ziarati et al, 2019;Botello et al, 2019;Saadati et al, 2020). Due to these low concentrations, some of these sites have been declared below the permissible limits, but in some cases, environmental problems persist affecting the growth and development of plants (Sánchez et al, 2017;Challenger et al, 2018). Hence, Soto et al (2018) and González-Mille et al (2019) highlight the importance of considering methods of identification of these components since they relate them to negative effects on water potential, density, and porosity of the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in similar studies of abandoned oil sites, infrastructure has been identified, such as valves, incinerators, separation batteries, wells, and waste pits (Trellu et al, 2017), all with very low concentrations of hydrocarbons and, in some cases, spills have been covered by flora or soil (Ziarati et al, 2019;Botello et al, 2019;Saadati et al, 2020). Due to these low concentrations, some of these sites have been declared below the permissible limits, but in some cases, environmental problems persist affecting the growth and development of plants (Sánchez et al, 2017;Challenger et al, 2018). Hence, Soto et al (2018) and González-Mille et al (2019) highlight the importance of considering methods of identification of these components since they relate them to negative effects on water potential, density, and porosity of the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Values refer to a system of beliefs or assumptions that guide actors' behaviors (Aasen & Vatn, 2018). Sustainable development will be defined through the approach promoted by the 2030 Agenda, which includes economic viability, social equity, environmental conservation and human security dimensions (Challenger et al, 2018; United Nations, 2015). Despite the fact that security is not traditionally considered a dimension within the SDGs or the 2030 Agenda, this project includes it for two reasons.…”
Section: Methodsmentioning
confidence: 99%
“…PROFEPA ( Procuraduría Federal de Protección al Ambiente ) is the agency responsible for the inspection of all major facilities subject to Mexico's General Law of Ecological Equilibrium and Environmental Protection ( Ley General de Equilibrio Ecológico y Protección al Ambiente ). Regulatory capacity is weak due to a lack of coordination between semi-autonomous agencies such as PROFEPA and the Ministry of the Environment (Challenger et al ., 2018).…”
Section: Datamentioning
confidence: 99%